Nonuniform Microtubular Polarity Established by CHO1/MKLP1 Motor Protein Is Necessary for Process Formation of Podocytes - Kobayashi, Naoto (The Rockefeller University Press, 1998)
Podocytes are unique cells that are decisively involved in glomerular filtration. They are equipped with a complex process system consisting of major processes and foot processes whose function is insufficiently understood (Mundel, P., and W. Kriz. 1995. Anat. Embryol. 192:385–397). The major processes of podocytes contain a microtubular cytoskeleton. Taking advantage of a recently established cell culture system for podocytes with preserved ability to form processes (Mundel, P., J. Reiser, A. Zúñiga Mejía Borja, H. Pavenstädt, G.R. Davidson, W. Kriz, and R. Zeller. 1997b. Exp. Cell Res. 36:248–258), we studied the functional significance of the microtubular system in major processes. The following data were obtained: (a) Microtubules (MTs) in podocytes show a nonuniform polarity as revealed by hook-decoration. (b) CHO1/ MKLP1, a kinesin-like motor protein, is associated with MTs in podocytes. (c) Treatment of differentiating podocytes with CHO1/MKLP1 antisense oligonucleotides abolished the formation of processes and the nonuniform polarity of MTs. (d) During the recovery from taxol treatment, taxol-stabilized (nocodazole- resistant) MT fragments were distributed in the cell periphery along newly assembled nocodazole-sensitive MTs. A similar distribution pattern of CHO1/MKLP1 was found under these circumstances, indicating its association with MTs. (e) In the recovery phase after complete depolymerization, MTs reassembled exclusively at centrosomes. Taken together, these findings lead to the conclusion that the nonuniform MT polarity in podocytes established by CHO1/MKLP1 is necessary for process formation.